Influence of Cochlear Implant Use on Perceived Listening Effort in Adult and Pediatric Cases of Unilateral and Asymmetric Hearing Loss. Issue 9 (October 2021) - Lopez, Erin M.; Dillon, Margaret T.; Park, Lisa R.; Rooth, Meredith A.; Richter, Margaret E.; Thompson, Nicholas J.; O'Connell, Brendan P.; Pillsbury, Harold C.; Brown, Kevin D.
Abstract : Objective: Assess the influence of cochlear implant (CI) use on the perceived listening effort of adult and pediatric subjects with unilateral hearing loss (UHL) or asymmetric hearing loss (AHL). Study design: Prospective cohort. Setting: Tertiary referral center. Patients: Adults and children with UHL or AHL. Intervention: Cochlear implantation. Subjects received their CI as part of a clinical trial assessing the effectiveness of cochlear implantation in cases of UHL and AHL. Main outcome measures: Responses to the Listening Effort pragmatic subscale on the Speech, Spatial, and Qualities of Hearing Scale (SSQ) or SSQ for Children with Impaired Hearing (SSQ-C) were compared over the study period. Subjects or their parents completed the questionnaires preoperatively and at predetermined postactivation intervals. For the adult subjects, responses were compared to word recognition in quiet and sentence recognition in noise. Results: Forty adult subjects (n = 20 UHL, n = 20 AHL) and 16 pediatric subjects with UHL enrolled and underwent cochlear implantation. Subjects in all three groups reported a significant reduction in perceived listening effort within the initial months of CI use ( p < 0.001; η 2 ≥ 0.351). The perceived benefit was significantly correlated with speech recognition in noise for the adult subjects with UHL at the 12-month interval ( r (20) = .59, p = 0.006). Conclusions: Adult and pediatric CI recipients with UHL or AHL report a reduction in listening effort with CI use as compared to their preoperative experiences. Use of the SSQ and SSQ-C Listening Effort pragmatic subscale may provide additional information about a CI recipient's experience beyond the abilities measured in the sound booth.